Efficacy and Safety of Stereotactic Radiotherapy in Cushing’s Disease: A Single Center Experience - Apaydin, Tugce; Ozkaya, Hande Mefkure; Durmaz, Sebnem Memis; Meral, Rasim; Kadioglu, Pinar (Experimental and Clinical Endocrinology & Diabetes, 2020)
Objective To determine the efficacy and safety of stereotactic radiotherapy (RT) in patients with Cushing’s disease (CD). Methods The study included 38 patients [31 patients who received gamma knife radiosurgery (GKS) and 7 patients who received cyberknife hypofractionated RT (HFRT)] with CD. Hormonal remission was considered if the patient had suppressed cortisol levels after low dose dexamethasone, normal 24-hour urinary free cortisol (UFC), and lack or regression of clinical features. Results Biochemical control after RT was observed in 52.6% of the patients with CD and median time to hormonal remission was 15 months. Tumor size control was obtained in all of the patients. There was no significant relationship between remission rate and laboratory, radiological and pathological variables except for preoperative UFC. Remission rate was higher in patients with lower preoperative UFC. Time to remission increased in parallel to postoperative cortisol and 1mg DST level. Although medical therapy before RT did not affect the rate of- and time to remission, medical therapy after RT prolonged the time to hormonal remission.Conclusion In this current single center experience, postoperative cortisol and 1mg DST levels were found as the determinants of time to remission. Although medical therapy before RT did not affect the rate of- and time to remission, medical therapy after RT prolonged the time to biochemical control . This latter finding might suggest a radioprotective effect of cortisol lowering medication use on peri-RT period.
Keywords: Cushing’s disease; cyberknife hypofractionated radiotherapy; gamma knife radiosurgery; stereotactic